Patient value: Perspectives from the advocacy community. (20th September 2017) - Addario, Bonnie J; Fadich, Ana; Fox, Jesme; Krebs, Linda; Maskens, Deborah; Oliver, Kathy; Schwartz, Erin; Spurrier‐Bernard, Gilliosa; Turnham, Timothy
Abstract: All health‐care systems are under financial pressure and many have therefore developed value frameworks to assist decision making regarding access to treatment. Unfortunately, many frameworks simply reflect the clinically focused values held by health‐care professionals rather than outcomes that also matter to patients. It is difficult to define one single homogeneous set of patient values as these are shaped by social, religious and cultural factors, and health‐care environment, as well as many factors such as age, gender, education, family and friends and personal finances. Instead of focusing on an aggregated set of values, frameworks should attempt to incorporate the broader range of outcomes that patients may regard as more relevant. Patient advocates are well placed to advise assessment bodies on how particular therapies will impact the patient population under consideration and should be closely involved in developing value frameworks. In this paper, a group of patient advocates explore the varying definitions of patient value and make positive recommendations for working together to strengthen the patient voice in this area. The authors call on framework developers, the patient advocacy and research communities, the health‐care industry and decision‐makers to undertake specific actions to ensure patient value is included in current and future value frameworks. This is justified on compassionate and economic grounds: better health outcomes result when patients receive treatment tailored to individual needs. Paying attention to the patient perspective also results in better use of resources—a goal that should appeal to all stakeholders.